Cold crystallization from chiral smectic phase. (1st February 2019) - Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Marzec, Monika; Urbańska, Magdalena; Tykarska, Marzena
ABSTRACT: Cold crystallization of liquid crystalline (S)-4'-(1-methylheptyloxycarbonyl) biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy) heptyl-1-oxy]-2-fluorobenzoate (3F7HPhF) was studied in isothermal as well as non-isothermal conditions. For isothermal conditions at temperatures between 233 and 250 K X-ray diffraction and differential scanning calorimetry were used. The crystallization kinetics was described by the Avrami–Avramov model, and the values of Avrami exponent, characteristic time and activation energy were determined. The kinetics of the cold crystallization in non-isothermal conditions for chosen heating rates up to 0.5 K/s was studied by differential scanning calorimetry and analyzed using Ozawa, Mo and Augis–Bennett models. Cold crystallization was found to be three-dimensional and controlled by diffusion both in the isothermal and non-isothermal process, however the activation energy determined in the non-isothermal process is about two times smaller than in the isothermal one.